Plant Protease Inhibitors in Therapeutics-Focus on Cancer Therapy - Srikanth, Sandhya; Chen, Zhong (Frontiers in Pharmacology, 2016)
Plants are known to have many secondary metabolites and phytochemical compounds which are highly explored at biochemical and molecular genetics level and exploited enormously in the human health care sector. However, there are other less explored small molecular weight proteins, which inhibit proteases/proteinases. Plants are good sources of protease inhibitors (PIs) which protect them against diseases, insects, pests, and herbivores. In the past, proteinaceous PIs were considered primarily as protein-degrading enzymes. Nevertheless, this view has significantly changed and PIs are now treated as very important signaling molecules in many biological activities such as inflammation, apoptosis, blood clotting and hormone processing. In recent years, PIs have been examined extensively as therapeutic agents, primarily to deal with various human cancers. Interestingly, many plant-based PIs are also found to be effective against cardiovascular diseases, osteoporosis, inflammatory diseases and neurological disorders. Several plant PIs are under further evaluation in in vitro clinical trials. Among all types of PIs, Bowman-Birk inhibitors (BBI) has been studied extensively in the treatment of many diseases, especially in the field of cancer prevention. So far, crops such as beans, potatoes, barley, squash, millet, wheat, buckwheat, groundnut, chickpea, pigeonpea, corn and pineapple have been identified as good sources of PIs. The PI content of such foods has a significant influence on human health disorders, particularly in the regions where people mostly depend on these kind of foods. These natural PIs vary in concentration, protease specificity, heat stability, and sometimes several PIs may be present in the same species or tissue. However, it is important to carry out individual studies to identify the potential effects of each PI on human health. PIs in plants make them incredible sources to determine novel PIs with specific pharmacological and therapeutic effects due to their peculiarity and superabundance.